La Scrittura nel Quarto Vangelo: una tappa della storia della ricerca (1860-2004) - Cavicchia, Alessandro (Liber annuus, 2017)
This article describes the history of the research on the use of Scripture in John's Gospel approximately from 1885 to 2004. The perspective adopted in this overview has identified four areas of interest and methodological approaches. The first area of studies is guided by the question of the textual origins of the Johannine use of Scripture in connection with the anti-Jewish character of the Fourth Gospel. The second area shows the gradual shift from the interest in textual origins towards the evaluation of the hermeneutics and techniques of the use of Scripture, particularly from the Jewish point of view. The third area of interest highlights the theological and Christological characters of the Johannine use of Scripture. The fourth adopts an intertextual and sociological approach. It is especially the sociological analysis that focuses on a sectarian and anti-Jewish orientation of the Fourth Evangelist.In this research report, the Johannine use of Scripture emerges as rich, multifaceted, and not reducible to one point of view. Consequently, it also requires a pluralistic methodological approach, able to combine textual, hermeneutical, theological, historical and sociological issues. The Jewish Scripture, which is almost identical to the Christian Old Testament, appears as the source of divine inspiration, able to offer guidelines for the interpretation of God and history. In the Johannine use of Scripture, a contradictory, “emptying”, or “destroying” attitude cannot be envisaged. On the contrary, the Fourth Gospel proclaims the full epiphany of the Word of God himself and the inner mystery of Scripture in Jesus the Nazarene as the embodied Logos. In this way, the Gospel of John shows its understanding of Scripture as a culminating point of this tradition. As appears clear in this contribution, Scriptural tradition and Christian faith continue to be crucial instruments for discussing and discerning the mystery of God down through the centuries.